Analysis of Community Health Center Capacity in Integrating Mental Health Screening into Antenatal Care Services: A Systematic Literature Review - Erika Khairani Siregar; Arih Diyaning Intiasari; Joko Mulyanto (Eduvest - Journal of Universal Studies, 2026)
Mental health disorders during pregnancy, including depression and anxiety, pose significant public health challenges affecting maternal, fetal, and child health outcomes. Although the integration of mental health screening into antenatal care (ANC) is recommended, implementation remains suboptimal due to constraints in health system capacity. This research aims to analyze community health center capacity in integrating mental health screening into ANC services through a systematic literature review. Following PRISMA guidelines, literature searches were conducted via Publish or Perish using Google Scholar, with the keywords "mental health screening" AND "antenatal care," and "maternal mental health" AND "antenatal care," yielding 18 articles that met the inclusion criteria for qualitative synthesis. Findings reveal that successful integration depends on six key factors: human resource capacity, service system integration, valid screening instruments, effective referral systems, maternal mental health literacy, and health technology support. Health worker training has been shown to improve competence in psychosocial assessment, while policy support, integrated service systems, and digital technology enhance screening effectiveness. This review concludes that community health center capacity is pivotal to the successful integration of mental health screening. Strengthening health worker competencies, supporting integrated service systems, providing standardized instruments, establishing effective referral mechanisms, and leveraging health technology are essential for comprehensive and sustainable improvement of maternal health services.